Modern perception of the Civil War: pedagogy as overcoming myths in mass consciousness - D. I. Petin; M. M. Stelmak (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the analysis of the activities of the Historical archives of the Omsk region connected with attempts to counteract its falsification through the exposition and excursion work of archivists. The authors come to the conclusion that there is a need in the cultural society for specialized scientific centers aimed simultaneously at popularizing history and our country